Leadership, Innovation and Community Participation Pillar of Institutionalization in Bank Sampah Induk Surabaya - Adawiah, Wardatul; Hanindraputri, Eufrasia Kartika; Muhammad Abid Kamalsyah (Journal of Social Dynamics and Governance, 2024)
Surabaya, the second largest city in Indonesia, has serious problems related to waste. The environmental crisis comes from high consumption, producing waste from households and industries. One of the environmental movements that is a local initiative to restore environmental problems in Surabaya is the Bina Bhakti Lingkungan Foundation. This foundation is present in Surabaya as a local initiative at the grassroots level to manage the environment, starting from managing the Bank Sampah Induk in Surabaya. This study analyzes leadership, innovation, and community participation in the Bank Sampah Induk in Surabaya, which the Bina Bhakti Lingkungan Foundation manages. This study uses a qualitative descriptive method with in-depth interview data collection techniques, observations and literature studies. The local initiative movement found in this Bank Sampah shows that collaboration between government, private business units, and community participation can strengthen the environmental movement’s institutional process in Surabaya. The results of this study show that the regulative, normative and cultural cognitive pillars have implications for reinforcing institutions internally. Meanwhile, the actor, innovation and community participation pillars have implications for strengthening institutions externally.